Effects of different rearing systems on growth and fattening performance of american bronze turkeys - Emre Arslan; Orhan Cetin (Eurasian Journal of Veterinary Sciences)
Aim: This study was carried out to investigate the effect of different rearing conditions on the growth and fattening performance of American bronze turkeys. Materials and Methods: In the study, data from a total of 123 American bronze turkeys were analyzed. The hatchlings, whose hatching weight was measured, were reared together for the first 10 weeks, and then divided into the experimental groups. The intensive rearing system group (control group) was fed only with concentrated ad libitum. Pasture groups are semi-intensive and extensive rearing systems. The semi-intensive group was subjected to 75% restricted feeding of the concentrate that the intensive group should consume. The turkey flock in the extensive rearing system was fed 50% of the feed that the turkeys in the intensive rearing system group should consume. Pasture groups benefited from the pasture between 09:00-17:00. The growth and fattening performances of the turkeys were examined by regular weighing and measurements every two weeks as they were being reared in these growing conditions between the ages of 10-32 weeks. Results: The 32-week live weights of turkeys were found to be 4.60-4.70 and 4.52 kg in females and 7.58-7.79 and 6.71 kg in males, in intensive, semi-intensive, and extensive systems, respectively. The effect of the rearing system was significant in males at 12-32 weeks, moreover, a difference was determined among groups in females at 14-28 weeks. Conclusion: As a result of, American bronze turkeys can be suitable breed for pasture conditions. Based on the live weight gain and feed efficiency values of the study groups, this breed can continue to grow for longer than 32 weeks when quality pastures are provided.